2017
DOI: 10.1167/17.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Face perception develops similarly across viewpoint in children and adolescents with and without autism spectrum disorder

Abstract: Atypical face perception has been associated with the socio-communicative difficulties that characterize autism spectrum disorder (ASD). Growing evidence, however, suggests that a widespread impairment in face perception is not as common as once thought. One important issue arising with the interpretation of this literature is the relationship between face processing and a more general perceptual tendency to focus on local rather than global information. Previous work has demonstrated that when discriminating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
1
2
0
Order By: Relevance
“…Examination of the primary studies corroborated these findings, showing that only two studies of the children/adolescent group versus nine in the adult group reported differences in amygdala. These findings are consistent with behavioral studies suggesting that impairments in face perception in ASD might not be present in childhood, but develop from the age of fifteen (Guy, Habak, Wilson, Mottron, & Bertone, 2017). Moreover, neuroimaging studies demonstrated that the neural network underpinning face perception undergoes a slow process of maturation during childhood and adolescence, including a blunted response of the amygdala in normally developing children (Behrmann, Scherf, & Avidan, 2016; Pfeifer et al., 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Examination of the primary studies corroborated these findings, showing that only two studies of the children/adolescent group versus nine in the adult group reported differences in amygdala. These findings are consistent with behavioral studies suggesting that impairments in face perception in ASD might not be present in childhood, but develop from the age of fifteen (Guy, Habak, Wilson, Mottron, & Bertone, 2017). Moreover, neuroimaging studies demonstrated that the neural network underpinning face perception undergoes a slow process of maturation during childhood and adolescence, including a blunted response of the amygdala in normally developing children (Behrmann, Scherf, & Avidan, 2016; Pfeifer et al., 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Viewpoint changes, however, also impair the ability to discriminate between novel, unfamiliar face identities (Favelle, Hill & Claes, 2017;Guy, Habak, Wilson et al, 2017;Habak, Wilkinson & Wilson, 2008;Lee et al, 2006;Meinhardt-Injac, Meinhardt & Schwaninger, 2009;Morin, Guy, Habak et al, 2015;Newell et al, 1999;Troje & Bülthoff, 1996;Wilson, Loffler & Wilkinson, 2002). The paradigms employed by these studies made minimal memory demands.…”
Section: Viewpoint-dependent Face Identificationmentioning
confidence: 94%
“…Importantly, however, the present study focused upon a small range of angular rotations (±20°), centered upon the frontal view. This ensured that the individual features of faces presented from the side were partially, rather than completely, obscured (Guy et al, 2017;Morin et al, 2015). In order to extrapolate our data to faces presented from larger viewing angles, one would need to assume that the relationship between viewing angle and face discrimination sensitivity remains linear beyond the range that we tested.…”
Section: Same Viewpointmentioning
confidence: 99%